Fish Diversity and Socio-Economic Status of Gomti River Fishermen at Cumilla Sadar Bangladesh (Bangladesh Journal of Zoology, 2024)
The Gomti River originates in eastern Tripura, India, and flows westward into Bangladesh, supporting a variety of fish species along its course. This study focused on evaluating the fish diversity and the socio-economic status of fishermen in the Gomti River at Cumilla Sadar Upazila, Cumilla, Bangladesh. Researchers identified 37 fish species from 5 orders and 15 families, with most species belonging to the Cypriniformes and Siluriformes orders. According to the IUCN Bangladesh (2015), 9 species were classified as near threatened, 3 as endangered, and 4 as vulnerable. The data included metrics such as species richness, the Shannon-Wiener diversity index, and species evenness. In July, the river's species richness was recorded at 32, the Shannon-Wiener diversity index at 3.30372, and species evenness at 0.66074. By December, these values decreased to 9 for species richness, 2.10556 for the Shannon-Wiener index, and 0.66423 for species evenness, reflecting a decline in fish diversity in the Gomti River. Information was also gathered through interviews with 30 randomly chosen fishermen and focus group discussions using a structured checklist. The findings showed that 54% of the fishermen had annual earnings between BDT 91,000 and 1,20,000. The majority of the fishermen were aged between 35 and 50 years, with 87% married, an average family size of 5-7 people, and mostly living in nuclear families. Additionally, 53% of the fishermen had education only up to the junior secondary level. Most fishermen depended on allopathic doctors for healthcare, and their living conditions, including housing and sanitation, were poor. Various indicators of livelihood suggest that the fishermen are living in dire conditions. To address these challenges, adopting community-based aquatic resource management strategies could boost fish production and improve the living standards of the communities along the Gomti River.Bangladesh J. Zool. 52(2): 185-199, 2024